A Gyssens Evaluation On Antibiotics Usage On Inpatients With Urinary Tract Infection In Hospital X, Central Jakarta, on January 2017 – June 2019: Gyssens Evaluation On Antibiotics Usage On Inpatients With Urinary Tract Infection In Hospital X, Central Jakarta, on January 2017 – June 2019 - Henny Tannady Tan; Ade Dharmawan; Agus Cahyadi; Nicolas Layanto; Elisabeth Harahap (Universitas Wiralodra, 2020)
Urinary tract infections are infections from the bladder to the renal parenchyma, and can affect all ages. Empirical therapy can reduce morbidity, but due to the use of antibiotics that are not appropriate will have an impact on resistance that will cause increase morbidity, mortality, and health costs. In the Southeast Asian region, high use of antibiotics were found almost more than 80% in various provinces in Indonesia. This study aims to assess the appropriatness use of antibiotics in hospitalized patients with UTIs in the District Hospital X in the period January 2017 - June 2019 using gyssens criteria. This is retrospective study. Research data sourced from medical records. Data was collected and assessed with Gyssens flow, then processed using Microsoft Excel. The results found 15 cases (46.88%) with the appropriate use (category 0), 3 cases (9.37%) incorrect interval (category IIB), 1 case (3.33%) incorrect dosage (category IIA ), 10 cases (31.25%) too short given (category IIIB), 3 cases (9.37%) too long given (category IIIA). Empirical therapy inpatients with diagnosis urinary tract infections atvDistrict Hospital X, 46.8% of antibiotics were used appropriately.